2017
DOI: 10.1097/opx.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Centration and Decentration of Contact Lenses during Peripheral Gaze

Abstract: Significance Varying amounts of peripheral defocus reported in previous studies are likely due whether peripheral defocus is measured while turning the eyes or the head. Contact lenses (CL) lag when viewing objects in peripheral gaze, so future studies ought to measure peripheral defocus while turning the head to measure defocus through the peripheral add power. Purpose Soft multifocal CL peripheral defocus studies report varying results. To determine whether soft multifocal CL lag when turning the eyes coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…This would contribute positively to the quality of vision and efficacy of the lens. 41,42 While we could not evaluate the impact of the reverse geometry on the peripheral defocus produced, this issue will be addressed in future work.…”
Section: Discussionmentioning
confidence: 99%
“…This would contribute positively to the quality of vision and efficacy of the lens. 41,42 While we could not evaluate the impact of the reverse geometry on the peripheral defocus produced, this issue will be addressed in future work.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large eye rotation will alter muscular stress as well as eyelid pressure on the eyeball, potentially causing optical changes, [251][252][253] although such changes have not been noted in more recent studies. [254][255][256] In the case of contact lenses, it should also be noted that El-Nimri and Walline 257 found that eye movements can cause shifts in soft contact lenses by more than 0.5 mm, and thus have the potential to affect peripheral refraction measurements. It is recommended that (where possible and without slowing measurement time) eye movements should be limited during peripheral refraction testing, especially when measuring at large angles.…”
Section: Exploratory Outcomesmentioning
confidence: 99%
“…Some studies have investigated contact lens centration on the eye. [21][22][23][24] As an example, El-Nimri and Walline 24 evaluated centration of a soft multifocal contact lens (centre-distance Proclear, CooperVision, www.coopervision. com) for primary gaze and 20°eye rotation.…”
Section: Introductionmentioning
confidence: 99%